Central Nervous System Demyelination in a Charcot-Marie-Tooth Type 1A Patient. (16th December 2013) - Koros, Christos; Evangelopoulos, Maria-Eleftheria; Kilidireas, Costas; Andreadou, Elisabeth
Abstract : Introduction . Central nervous system involvement, either clinical or subclinical, has been reported mainly in X-linked Charcot-Marie-Tooth (CMT-X) patients. Case Presentation . We present the case of a 31-year-old man with a genetically confirmed history of CMT1A who developed CNS involvement mimicking multiple sclerosis (MS). Clinical, imaging, and laboratory findings suggested an autoimmune CNS demyelination. Discussion . Although the simultaneous existence of CMT1A and MS could be coincidental we postulate that overexpression of PMP22, the target protein in CMT1A, might influence the immunological self-tolerance to CNS proteins via molecular mimicry, leading to a CNS autoimmune demyelinating disorder.